(untitled) - Snyder, Brad (Chicago, 2003)
Beyond a doubt this is a well documented, interesting to read, important addition to the history of black baseball in America.
Keywords: Baseball,African American baseball players,Discrimination in sports; History,History; 20th century,20th century; Washington (D.C.),Washington (D.C.),United States